LBX2-AS1 Activates FSTL3 by Binding to Transcription Factor RARα to Foster Proliferation, Migration, and Invasion of Thyroid Cancer - Li, Jia; Shen, Jie; Qin, Lan; Lu, Dongyan; Ding, Enci (Frontiers in Genetics, 2021)
Background: Thyroid cancer is a frequent endocrine tumor in women. It is of great significance to investigate the molecular mechanism of progression of thyroid cancer. Methods: Gene expression data set and clinical data were downloaded from TCGA database for differential expression analysis. The triplet of downstream transcription factors (TFs) and modulatory genes of target lncRNA in thyroid cancer was predicted by the lncMAP database. mRNA and protein expression of lncRNA LBX2-AS1, RARα and FSTL3 were detected by qRT-PCR and western blot. The localization of lncRNA LBX2-AS1 in cells was tested by FISH assay. The RIP assay was applied to verify the binding relationship between lncRNA LBX2-AS1 and FSTL3. ChIP and dual-luciferase assays were used to prove the binding relationship between RARα and FSTL3. Cell function experiments were used to test cell proliferation, migration and invasion in each treatment group. The role of lncRNA LBX2-AS1 in thyroid cancer progression was also confirmed in nude mice. Results: Bioinformatics analysis indicated that lncRNA LBX2-AS1, RARα, FSTL3 were remarkably fostered in thyroid cancer tissue, and LBX2-AS1 was evidently correlated with clinical features. The LncMAP triplet prediction showed that LBX2-AS1 recruited TF RARα to modulate FSTL3. RIP assay confirmed that LBX2-AS1 was prominently enriched on RARα. ChIP and dual-luciferase report assays unveiled that RARα bound to the promoter region of FSTL3 and functioned as a TF. Cell function experiments uncovered that LBX2-AS1 boosted the progression of thyroid cancer. The rescue experiments showed that LBX2-AS1 recruited the TF RARα to hasten the transcription activity of FSTL3 and thus promoted the development of thyroid cancer. Conclusion: The integrative results demonstrated that LBX2-AS1 activated FSTL3 by binding to TF RARα to hasten proliferation, migration and invasion of thyroid cancer.